RESEARCH OF LOW-TEMPERATURE, HARMONIZED HEATING SYSTEMS USING SOLAR ENERGY FOR BUILDINGS (Web of Technology: Multidimensional Research Journal, 2024)
In the world, special attention has recently been paid to increasing the scale of practical use of renewable energy sources, as well as saving hydrocarbon fuel and energy resources and rational use of energy resources by increasing the efficiency of heat generating equipment. Currently, in developed countries, "the production of thermal energy based on renewable energy sources is growing by 6% per year, of which the share of solar energy is 58%."1 From the point of view of achieving these indicators in the implementation of energy saving programs in the field of construction of buildings and structures, the development of engineering approaches aimed at rational use of energy, as well as the transition to renewable energy sources, becomes an important task.